Ewolucja miejsca i roli audytu wewnętrznego w przedsiębiorstwie - Bednarek, Piotr (Evolution of Internal Audit Place and Role in an Enterprise, 2007)
Internal audit has been functioning in Polish enterprises for relatively short time. That is way in the paper history of internal audit in other countries, especially the United States of America, it is analyzed from the point of view of its place and role in an enterprise. Moreover the author compares the rhetoric of the associations trying to professionalize the activity with the changes which occur in the work of internal auditors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 25-31